Peran Green Banking sebagai pemoderasi pada Determinan Kinerja Keuangan Bank Umum Syariah Periode 2018-2022 - Ai’ni Rahma Dewi, Siska; Pamungkas, Imang Dapit (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research examines and analyses the influence of solvency, profitability, and Murabaha financing on financial performance with green banking as moderation. Financial performance is measured using a combined SCnP model. The data is from a purposive sampling of all BUS registered in OJK during 2018-2022. Data were analyzed using SEM PLS via Warp PLS v 7.0. The research output shows that all of the independent variables, only solvency, have positively influenced financial performance. The moderating variable green banking can strengthen the influence of solvency and Murabaha financing on financial performance but cannot strengthen the influence of profitability on financial performance.